Tight Binding Modelling of Energy Band Structure in Nitride Heterostructures - Uenlue, Hilmi; Akinci, Oezden; Guerel, Hi̇kmet Hakan (American Scientific Publishers, 2008)
We studied the electronic structure of group III–V nitride ternary/binary heterostructures by using a semi-empirical sp3s* tight binding theory, parametrized to provide accurate description of both valence and conductions bands. It is shown that the sp3s* basis, along with the second nearest neighbor (2NN) interactions, spin-orbit splitting of cation and anion atoms, and nonlinear composition variations of atomic energy levels and bond length of ternary, is sufficient to describe the electronic structure of III–V ternary/binary nitride heterostructures. Comparison with experiment shows that tight binding theory provides good description of band structure of III–V nitride semiconductors. The effect of interface strain on valence band offsets in the conventional Al1−xGaxN/GaN and In1−xGaxN/GaN and dilute GaAs1−xNx/GaAs nitride heterostructures is found to be linear function of composition for the entire composition range (0 ≤ x ≤ 1) because of smaller valence band deformations.